State-of-the-Art Functional Biomaterials in China (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
China has become a leader in the research, development, and commercialization of various biomaterials and medical devices. This Special Issue will highlight the cutting-edge progress achieved in recent years by the Chinese biomaterial community, showcasing state-of-the-art functional biomaterials in this context. Its scope includes but is not limited to the following: advanced multifunctional biomaterials; state-of-the-art antibacterial surfaces; methodologies in material biology; innovations in probing bio–nano interfaces; immunomodulatory strategies for implantable devices; clinical studies associated with the application of biomaterials; and other issues associated with biomaterials and biomedical devices.